Babymed: pulse oximeter adapted to premature babies with low cost crib death detection - Valenzuela Guerra, Andrea Alejandra (2020)
The pulse oximeter is a non-invasive device that allows you to determine the percentage of oxygen saturation in the blood using photoelectric methods. This is an indispensable tool in neonatology, mainly in premature babies. A premature baby is a baby born before 37 complete weeks of gestation and, in general, may have problems breathing and maintaining stable body temperature. Therefore, they need to have greater control and monitoring of their vital signs by a doctor or their mother. Premature babies tend to have cardiovascular and respiratory problems during their first few months of development. That's why a pulse oximeter was created for premature babies, which uses a non-invasive method, detects the decrease in oxygen saturation levels out of the ordinary, and then sends a type of signal or alarm to the mother, portable to keep at home. Besides, it monitors oxygen saturation through a computer interface and allows a patient's medical history to be saved. Also, the device is low-cost for greater outreach among low-income communities.